Level of awareness regarding the tribunal for consumer claims Malaysia among the students of Universiti Teknologi Malaysia - 388822 Mohamed Raisul Islam Mohamed Haniffa; Khairiah Soehod, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2009)
Project Paper (Sarjana Muda (Pengurusan - Pemasaran)) - Universiti Teknologi Malaysia, 2009